NGHIÊN CỨU TÍNH CHẤT ỨC CHẾ CỦA MUỐI XÊRI ĐỐI VỚI QUÁ TRÌNH ĂN MÒN THÉP TRONG MÔI TRƯỜNG NƯỚC - Thanh Huyền, Bùi Thị; Bích Thuỷ, Hoàng Thị; Hiệu, Phạm Ngọc (Vietnam Journal of Chemistry, 2012)
This paper deals with the study of Ce3+ compound (CeCl3) as a non-toxic alternative to chromate for inhibition of mild steel in neutral water environment. Corrosion rates of mild steel in water with various concentrations of Ce3+ were determined. Electrochemical and non-electrochemical techniques have been used, such as linear polarization, potentialdynamic, EIS, weight-loss-test. The optimal concentration of the Ce3+ inhibitor is 500 ppm.